Flavodiiron Protein Substitutes for Cyclic Electron Flow without Competing CO2 Assimilation in Rice . Issue 2 (14th December 2017) - Wada, Shinya; Yamamoto, Hiroshi; Suzuki, Yuji; Yamori, Wataru; Shikanai, Toshiharu; Makino, Amane
Abstract : A moss flavodiiron protein can substitute the function of cyclic electron transport around photosystem I without any decrease in CO2 assimilation or biomass production in rice. Abstract: Flavodiiron protein (FLV) mediates photoreduction of O2 to H2 O. It is conserved from cyanobacteria to gymnosperms but not in angiosperms. The introduction of a moss ( Physcomitrella patens ) FLV ( PpFLV ) gene into Arabidopsis ( Arabidopsis thaliana ) made photosystem I (PSI) resistant to fluctuating light. Here, we used the same strategy with three rice ( Oryza sativa ) genotypes. PpFLV in the wild-type rice background functioned as an efficient PSI electron sink and increased resistance to PSI photodamage under fluctuating light. The introduction of PpFLV into the PGR5 -RNAi mutant [defective in PROTON GRADIENT REGULATION5 (PGR5)-dependent cyclic electron transport around PSI, CET-PSI], the crr6 mutant [defective in chloroplast NAD(P)H-dehydrogenase-like complex (NDH)-dependent CET-PSI], and the PGR5 -RNAi crr6 double mutant (double defective in CET-PSI activity) alleviated PSI photodamage under fluctuating light. Furthermore, PpFLV substituted for the function of PGR5- and NDH-dependent CET-PSI without competing for CO2 assimilation under constant light, as there was no difference in CO2 assimilation per Rubisco content and biomass production was recovered to the wild-type level. Thus, the exogenous FLV system could act not only as a safety valve under fluctuating light, but also generate a proton motive force for balancing the ATP/NADPH production ratio during steady-state photosynthesis.